الانطباعات الذهنية للمدن الكبرى :‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪ ‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪دراسة عن القاهرة /‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪ - عوف، أحمد محمد صلاح الدين أحمد،‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪‪
This Thesis Deals With Image Of Urban Areas With An Implementation On Cairo As Study Case The Research Was Fulfilled Through An Academic Study Of The Historic Development And Urban Growth Of Cairo So As To Recognize The Major Elements Forming Its Image The Research Determined These Elements Through Both: The Study Of The Urban History Of Cairo.